2014
DOI: 10.1111/scd.12078
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐related stigma in the dental setting: a qualitative study

Abstract: Purpose To explore the experiences and expectations of HIV‐related stigma in dental settings. Methods This was a cross‐sectional study of 60 HIV+ adult volunteers. We conducted audio‐recorded interviews; responses to four open‐ended questions were analyzed qualitatively for theme and content. Results Twenty‐seven participants (45%) reported ever having anticipated being judged, stigmatized or treated with disrespect in a dental setting due to HIV status. Thematic response categories included concerns about: (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 30 publications
2
22
0
1
Order By: Relevance
“…Similar to previous reports on PLHIV, the present study identified the enabling predictors, mostly related to the financial affordability and resources (see Table 2), which are also key factors in dental care utilization by other Canadians (7,10,14,20,21). In fact, according to the A&N model, these enabling factors can play an essential role in increasing one's access to dental care (9).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Similar to previous reports on PLHIV, the present study identified the enabling predictors, mostly related to the financial affordability and resources (see Table 2), which are also key factors in dental care utilization by other Canadians (7,10,14,20,21). In fact, according to the A&N model, these enabling factors can play an essential role in increasing one's access to dental care (9).…”
Section: Discussionsupporting
confidence: 84%
“…Approximately one-third of the 185 participating PLHIV visited a dental professional within the last year, which is lower than for the average Canadians (10,14). For almost half of the participants, the main reason for the dental visit was an emergency, and almost half reported unmet dental treatment needs, a similar pattern was found by Fox et al (2012) when studying access to dental care in PLHIV, by Jessani et al (2016) when studying access to dental care by vulnerable pregnant women, and by Bedos et al (2003) when discussing the lack of access to dental care by those living on welfare assistance (7,11,15,16).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…A central strength of this approach is that it was developed for HIV+ adults at high risk for oral disease [45]; commonly, such patients had concomitant illnesses (i.e., were medically complex), and had some level of economic and/or psychosocial strain as well as concerns about stigma, confidentiality, and whether they would be treated with respect by their health care providers [96]. In many ways, such a population represents an ideal prototype—as individuals in this population can present with a concentration of health issues (that might otherwise be seen across several different people).…”
Section: Integrative Oral Health Coaching Approach: Strengths and Limmentioning
confidence: 99%